1995
DOI: 10.1123/tsp.9.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Sport Consultation: An Evaluation of a Season-Long Intervention with Female Collegiate Gymnasts

Abstract: Applied sport consultants continue to offer intervention programs to athletes; however, research determining the efficacy of such programs has been lacking. This paper (a) briefly describes a season-long, multidimensional sport psychology intervention with a collegiate women’s gymnastics team, and (b) presents the results of the evaluation, examining the effectiveness of the program in reducing competitive state anxiety and increasing team cohesion, the two areas of evaluative focus. Results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…Moreover, the use of multidimensional tools in the literature remains scarce. Often, only one or two mental skills were appraised, such as state anxiety and self-confidence (Savoy, 1997), team cohesion and competitive state anxiety (Cogan & Petrie, 1995), imagery skills (Rodgers, Hall, & Buckolz, 1991) or focusing (Bakker & Kayser, 1994). Finally, the duration of the interventions in the single research design studies ranged from three days (Patrick & Hryckaiko) to 12-week investigations (Shambrook & Bull, 1996).…”
mentioning
confidence: 99%
“…Moreover, the use of multidimensional tools in the literature remains scarce. Often, only one or two mental skills were appraised, such as state anxiety and self-confidence (Savoy, 1997), team cohesion and competitive state anxiety (Cogan & Petrie, 1995), imagery skills (Rodgers, Hall, & Buckolz, 1991) or focusing (Bakker & Kayser, 1994). Finally, the duration of the interventions in the single research design studies ranged from three days (Patrick & Hryckaiko) to 12-week investigations (Shambrook & Bull, 1996).…”
mentioning
confidence: 99%
“…The techniques most used include goal setting, relaxation, arousal regulation, imagery, and thought control (self-talk and affirmation) (e.g., Defrancesco & Burk, 1997;Gould, Tammen, Murphy, & May, 1989;Taylor, 1995). Numerous studies have reported the favorable effects of psychological skills training programs on competitive performance (e.g., Cogan & Petrie, 1995;Garza & Feltz,1998;Grouios, 1992;Kendall, Hrycaiko, Martin, & Kendall, 1990, Li-Wei, Qi-Wei, Orlick, & Zitzelsberger, 1992, and on particular psychological indexes such as states of somatic and cognitive anxiety (Bakker & Kayser, 1994;Cogan & Petrie, 1995;Terry, Mayer, & Howe, 1998), self-confidence (Bakker & Kayser, 1994;Garza & Feltz, 1998;Terry, Mayer, & Howe, 1998), imagery ability (Rodgers, Hall, & Buckolz, 1991), and team cohesion (Savoy, 1997).…”
mentioning
confidence: 99%
“…Studies indicated that enough long duration PST program significantly increased experimental groups" team cohesion through the use of and the realization of the importance of setting common goals, and other methods applied could enhance the team cohesion level by putting all athletes in the exact ways (goals) to reach the teams goal (Burton, 1989;Brawley et al, 1993;Cogan and Petrie 1995;Voight and Callaghan 2001;Carron et al, 2002;Stevens and Bloom 2003;Senecal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%